Pendampingan Pembelajaran Al-Qur’an Bagi Para Pedagang Pasar Pengkolan Pasawahan Kidul Kec. Pasawahan Kab. Purwakarta - Dede Kurnia, Asep; Jalaludin, Jalaludin; Novita, Diana (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on the results of temporary observations, it was found that many Pengkolan Pasawahan Kidul traders who read the Qur'an were still haltingly, the reasons were various, there was a reason that they were busy with their respective trading businesses, so they did not take the time to read the Qur'an. The next reason is because from a young age he was not fluent in reading the Qur'an, because his parents did not pay attention to the education of the Qur'an, until he was carried away until now. The results of community service with the theme of Al-Qur'an Learning Assistance for Traders at the Pasar Pengkolan Pasawahan Purwakarta through several methods and approaches. For traders who are still illiterate in Arabic (hijaiyah), the PKM team uses the Baghdadiyah method, which is also known as the "spelling" method. For traders who are still stammering, the PKM team uses the iqra method, namely reading the Koran without spelling it, reading it directly with the pronunciation, it is hoped that it will be practiced often even though it is still halting it will get smoother. Not only that, the PKM team uses the tilawati method for traders who are already quite fluent in reading the Qur'an, it is hoped that the introduction of this method can add to the advice of reading the Qur'an for traders at Pengkolan Market, Pasawahan Purwakarta. Furthermore, for traders at Pasar Pengkolan Pasawahan Purwakarta who are already fluent in reading the Qur'an, the PKM team asked for their help to become tutors in the "bandungan" system for traders who were not fluent in reading the Qur'an